Ecotheology : voices from South and North - Hallman, David G. (WCC Publications, Geneva, Switzerland, Maryknoll, NY, Orbis Books, 1994)
"A new and urgent item on the agenda of churches around the world is the theological and ethical dimensions of the ecological crisis. Highlighted by the United Nations "Earth Summit" in Brazil, the issues covered in this volume raise unavoidable and fundamental questions of life-style and Christian witness in the face of threats to the very survival of humankind and planet Earth." "The ground-breaking essays by more than two dozen contributors in this book are divided into five sections: biblical witness, theological challenges, insights from ecofeminism, insights from indigenous people and ethical implications."--Jacket.
Beyond "North/South dialogue" / David G. Hallman -- The prophet of environment and development / Jose Pepz M. Cunanan -- Covenant, praise and justice in creation : five Bible studies / Margot Kassmann -- Creation and restoration : three biblical reflections / Renthy Keitzar -- A theological response to the ecological crisis / K.C. Abraham -- Social ecology : a timely paradigm for reflection and praxis for life in Latin America / Tony Brun -- Orthodoxy and the ecological crisis
Includes bibliographical references.
Keywords: Human ecology -- Religious aspects -- Christianity; Environmental protection -- Moral and ethical aspects; Environmental protection -- Developing countries; Indigenous peoples -- Attitudes; Ecofeminism